Trends in Hospitalization for Fall-Related Injuries in US Older Adults, 2001–2021 - Carlos H. Orces (The Scientific World Journal)
Conclusion: Hospitalizations for fall-related injuries significantly increased in US older adults over the past two decades. The present findings underscore the importance of implementing effective community-based programs to prevent fall-related injuries.